Antioxidant Activity Snack bar Composite Flour Banana Goroho (Musa acuminate) Purple Sweet Potato Flour (Ipomoea batatas L.) And Green Beans (Vigna radiata) - Ruth Eunike Nadine Bentelu; Dekie Rawung; Erny J. N. Nurali (Jurnal Agroekoteknologi Terapan, 2023)
The study of Antioxidant Activity Snack bar Composite Flour Banana Goroho (Musa acuminate) Purple Sweet Potato Flour (Ipomoea batatas L.) And Green Beans (Vigna radiata) aimed to (1) quantify the antioxidant activity of snack bars composite flour banana goroho, purple sweet potato flour and green beans (2) examine the physical properties of snack bars composite flour of banana goroho flour, purple sweet potato flour and green beans. The method used in this study was a Completely Randomized Design (CRD). The results of the research on the antioxidant activity of snack bars of goroho banana composite flour, purple sweet potatoes and green beans produced has antioxidant abilities that are classified as moderate to weak categories ranging from 248,57 ppm - 346,17 ppm. The color of the snack bar produced in treatment A, - 9 - treatment B, treatment C is Dark brown: Orange and Brown: Orange in treatment D. Snack bar color is based on L (brightness level) average of 28.87-42.73, based on a* level (red color dimension) average 10.70-13.47, based on average b* (yellow color dimension) level 16.03-21.27. The average level of hardness of snack bars is 23.71-34.9 mm/g/sec. Keywords: Antioxiants, Goroho Banana Flour, Purple Sweet Potato Flour, Snack bar Abstrak Penelitian Aktivitas Antioksidan Snack bar Tepung Komposit Pisang Goroho (Musa acuminate) Tepung Ubi Jalar Ungu (Ipomoea batatas L.) Dan Kacang Hijau (Vigna radiata) bertujuan untuk (1) mengukur aktivitas antioksidan snack bar tepung komposit pisang goroho, tepung ubi jalar ungu dan kacang hijau (2) menguji sifat fisik snack bar tepung komposit pisang goroho, tepung ubi jalar ungu dan kacang hijau. Metode yang digunakan dalam penelitian ini yaitu Rancangan Acak Lengkap (RAL). Hasil penelitian aktivitas antioksidan snack bar tepung komposit pisang goroho, ubi jalar ungu dan kacang hijau dihasilkan memiliki kemampuan antioksidan yang tergolong dalam kategori sedang hingga lemah berkisar antara 248,57 ppm - 346,17 ppm. Warna snack bar berdasarkan L (tingkat kecerahan) rata-rata 28,87-42,73, berdasarkan tingkat a* (dimensi warna merah) rata-rata 10,70-13,47, berdasarkan tingkat b* (dimensi warna kuning) rata-rata 16,03-21,27. Tingkat kekerasan snack bar rata-rata 23,7134,9 mm/g/detik. Kata Kunci: Antioksidan, Tepung Pisang Goroho, Tepung Ubi Jalar Ungu, Snack bar